Next-generation probiotic candidates targeting intestinal health in weaned piglets: Both live and heat-killed Akkermansia muciniphila prevent pathological changes induced by enterotoxigenic Escherichia coli in the gut - Lan, Cong; Li, Hua; Shen, Yuqing; Liu, Yang; Wu, Aimin; He, Jun; Cai, Jingyi; Tian, Gang; Mao, Xiangbing; Huang, Zhiqing; Yu, Bing; Zheng, Ping; et al. (Animal Nutrition, 2024)
The use of next-generation probiotics (NGP) in pigs for combating diseases has been subject to limited research. Here we explored the potential of a well-known NGP candidate Akkermansia muciniphila targeting pig gut health. In the first screening experiment, we found that the abundance of A. muciniphila peaked at 14 d old but decreased at weaning (21 d old; P < 0.05), suggesting the weaning period may be an effective window for A. muciniphila intervention. Following that, 48 crossbred weaned pigs at 28 d old were randomly assigned to five groups: control (CON), high/low live A. muciniphila (HA/LA), and high/low heat-killed A. muciniphila (HIA/LIA). From 1 to 28 d old, the CON group received gastric infusion of anaerobic sterile saline every other day; the HA and LA groups were gavaged every other day with 1 × 1010 CFU/5 mL and 5 × 108 CFU/5 mL live A. muciniphila, respectively; and the HIA and LIA groups were gavaged every other day with 1 × 1010 CFU/5 mL and 5 × 108 CFU/5 mL heat-killed A. muciniphila, respectively. At d 29, pigs in the CON group were randomly and equally divided into two groups, one of which was named the enterotoxigenic Escherichia coli (ETEC) group, and all groups except CON received a 5-d ETEC challenge. The supplementation of A. muciniphila numerically reduced the diarrhea rate of weaned pigs compared to the pigs that only received the ETEC challenge (P = 0.57), but the LIA group had a higher diarrhea rate than the CON group (P < 0.05). Consistent with this, the supplementation of A. muciniphila improved the small intestinal morphology and structure, proportion of CD4+ T lymphocytes in the blood, as well as the expression of genes related to intestinal barrier and antioxidant indices of pigs with ETEC challenge, especially for the LA group (P < 0.05). Meanwhile, A. muciniphila supplementation reduced the expression of ETEC virulence factor genes in the ileum and colon of pigs challenged by ETEC (P < 0.05). Therefore, A. muciniphila may protect the intestinal health of weaned piglets from damage caused by ETEC infection, but the effect may vary depending on the concentration and activity of A. muciniphila.